Latin America and Its “Reverse Gatopardism”: For Everything to Remain the Same, Nothing Can Change. a Middle-Income or a Neoliberal Trap?; [América Latina y Su “Gatopardismo a la Inversa”: Para Que Todo Pueda Seguir Igual, Nada Puede Cambiar. ¿Trampa del Ingreso Medio O “Trampa Neoliberal”?] - Palma-Penco, J (Fondo de Cultura Economica, 2025)
Krugman identified the puzzle of Latin America’s underperformance as one of the greatest challenges of economic theory. This paper investigates this challenge by analysing what we call Latin America’s “trilogy of contrasts”: compared to other regions, 1) its job creation (especially services) ranks first in the world; 2) but its productivity growth ranks last; and 3) as the income share of the rich remains among the highest, while investment rates became the lowest, the gap between the two has also become the largest in the world. The essence of my response to Krugman’s challenge is that these extremes are facets of the same phenomenon: getting stuck in “more of the same” when both post-1980 productivity strategies became exhausted, as they had already delivered their productivity growth potentials. This happened in the “extractivism” of the South and the “manufacturing assembly platform” of the North. What is needed now is to revitalize them with new drivers of productivity growth, such as the transition to processing raw materials, and the “anchoring” of assembly operations in the domestic economy—plus a “green new deal” and the transfer of the new technological paradigm to the entire economy. Trying to extend the “shelf life” of what is already exhausted is a recipe for falling into the middle-income trap—“more of the same” in either productive strategy is no longer a valid development option. However, structural rigidities, market distortions (domestic and international), and the region’s perennial ideological neophobia have so far blocked the “reengineering” of what is exhausted. © 2025 Fondo de Cultura Economica. All rights reserved.